PENGARUH STRUKTUR MODAL, KEPEMILIKAN MANAJERIAL, DAN LIKUIDITAS TERHADAP KINERJA KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Audi M, Neysa; Marlina, Evi; Samsiah, Siti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
This study aims to analyze the effect of capital structure, liquidity, and managerial ownership on financial performance with company size as a moderating variable in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. Data obtained from annual reports through www.idx.co.id. The research population includes 111 companies, with purposive sampling technique producing 34 companies as samples for three years of observation, so that the total research data is 102 data. The analysis was conducted using the moderated regression analysis (MRA) method with SPSS 25. The results showed that capital structure and liquidity affect financial performance, while managerial ownership has no effect. MRA test shows that firm size moderates the relationship between capital structure and liquidity on financial performance, but does not moderate the relationship between managerial ownership on financial performance. Thus, capital structure and liquidity play an important role in financial performance, while managerial ownership has no significant effect.